Effects of dentin dry/moist condition on the immediate adhesive performance of different solvent-based etch-and-rinse adhesivesystems - Silveira Machado, Lucas [UNESP]; De Oliveira, Fernanda Garcia [UNESP]; Andrade Guinossi, Thiago [UNESP]; Sundfeld Neto, Daniel; De Alexandre, Rodrigo Sversut; Figueiredo Reis, André; Sundfeld, Renato Herman [UNESP] (Elsevier, 2013)
Purpose: The purpose of this research was to analyze and measure, under optical microscopy, the hybrid layer thickness and resin tags length, as well as the microtensile bond strength of two conventional adhesive systems when applied to dry and moist dentinal substrate. Methods: Thirty-two extracted human molars were randomly distributed into four groups according to the adhesive systems (XP Bond and Prime&Bond 2.1) and moisture condition (dry and moist). In Groups I and II, XP adhesive system was applied on dry and moist dentin, respectively; while Groups III and IV received PB adhesive system, in the same way as was done in Groups I and II, respectively. After adhesive and restorative procedures, all specimens were sectioned along their long axes; one hemi-tooth sample was subjected to the microtensile bond strength test while the other was decalcified and serially sectioned into six micron thick slices and sequentially mounted on glass slides. These sections were stained by the Brown and Brenn method for posterior analysis and measurement of the hybrid layer and resin tags under a light microscope with a micrometric ocular 40/075. Results: Data were analyzed using two-way ANOVA and Tukey's test (α=0.05). For the variable hybrid layer thickness, XP showed no significant differences between dry and moist dentin (5.2 μm and 5.5 μm, respectively), but for PB, hybrid layer was significantly thicker for moist (4.0 μm) than for dry dentin (3.0 μm). For the variable resin tags length XP showed 17.9 μm length for dry dentin and 20.8 μm for moist dentin; PB 11.7 μm for dry and 12.69 μm for moist dentin;there was no significant differences between them, independent of the moisture condition. For the variable microtensile bond strength, XP showed 38.0 MPa for dry dentin and 44.5 MPa for moist dentin; and PB showed 22.7 MPa for dry dentin and 20.8 MPa for dry dentin no significant difference was observed between moist and dry dentin for XP (p=0.2) and PB (p=0.7), but XP was presented significantly higher bond strength values than PB in both moisture conditions (p=0.003 for dry and p=0.002 for moist). Conclusion: The two-step butanol-based etch-and-rinse adhesive XP Bond presented a superior behavior with regard to the hybrid layer thickness, length of resin tags and bond strength to dry and moist dentin substrates when compared with two-step acetone-based adhesive system Prime&Bond2.1. © 2013 Elsevier Ltd.
Keywords: Adhesive systems; Dry dentin; Hybrid layer; Microtensile bond strength; Moist dentin; Tags; Micro-tensile bond strength; Acetone; Bond (masonry); Bond strength (materials); Moisture; Optical microscopy; Substrates; Resins